Efektivitas Komunikasi Digital Terhadap Peningkatan Jumlah Pelanggan Pada Studio Estetika.id - Juang Kelana P. Meliala; Selamat Riadi (Journal of Education, Humaniora and Social Sciences (JEHSS), 2025)
Advances in digital technology have changed marketing strategies, especially in the photography services industry. This study aims to analyze the effectiveness of digital communication in increasing the number of customers of Studio Estetika.id, a photography service company in Medan that utilizes digital platforms in its marketing. The research method used is descriptive quantitative with data collection through a Likert scale questionnaire distributed to Studio Estetika.id customers. The sample was determined by the Taro Yamane formula and purposive sampling. The data was analyzed using validity and reliability tests with SPSS. The results of the study show that digital communication through social media, quality content, and active interaction contribute significantly to the increase in customers. Instagram is effective in building brand awareness and attracting new customers. Responsive interactions also increase customer trust, despite challenges such as stiff competition, budget constraints for paid advertising, and expanding branding strategies. This research recommends optimizing digital marketing, content innovation, and automating customer interactions to improve Studio Estetika.id's competitiveness and customer reach.